Vitamin D supplement on prevention of fall and fracture: A Meta-analysis of Randomized Controlled Trials - Thanapluetiwong, Saran; Chewcharat, Api; Takkavatakarn, Kullaya; Praditpornsilpa, Kearkiat; Eiam-Ong, Somchai; Susantitaphong, Paweena (Medicine (Baltimore), 2020)
Vitamin D supplement is one of the current possible interventions to reduce fall and fracture. Despite having several studies on vitamin D supplement and fall and fracture reductions, the results are still inconclusive. We conducted a meta-analysis to examine the effect of vitamin D supplement in different forms and patient settings on fall and fracture. A systematic literature research was conducted in MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials to identify randomized controlled trials (RCTs) to compare the effects of vitamin D supplements on fall and fracture outcomes. Random-effect models were used to compute the weighted mean difference for continuous variables and the risk ratio for binary variables. Forty-seven RCTs with 58,424 participants were identified reporting on fall outcome. Twenty-four of 47 studies with 40,102 subjects also reported fracture outcome. Major populations were elderly women with age less than 80 years. Overall, vitamin D supplement demonstrated a significant effect on fall reduction, RR = 0.948 (95% CI 0.914-0.984; P = .004, I = 41.52). By subgroup analyses, only vitamin D with calcium supplement significantly reduce fall incidence, RR = 0.881 (95% CI 0.821-0.945; P < .001, I = 49.19). Vitamin D3 supplement decreased incidence of fall but this occurred only when vitamin D3 was supplemented with calcium. Regarding fracture outcome, vitamin D supplement failed to show fracture lowering benefit, RR = 0.949 (95% CI 0.846-1.064; P = .37, I = 37.92). Vitamin D along with calcium supplement could significantly lower fracture rates, RR = 0.859 (95% CI 0.741-0.996; P = .045, I = 25.48). The use of vitamin D supplement, especially vitamin D3 could reduce incidence of fall. Only vitamin D with calcium supplement showed benefit in fracture reduction.